PENGARUH UANG ELEKTRONIK (E-MONEY) DAN UANG KARTAL (M0) TERHADAP PERPUTARAN UANG (VELOCITY OF MONEY) DI INDONESIA TAHUN 2010-2021 - , Yelly Zamaya, Koriyana Depi Andra ,Any widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
his study aims to find out the influence of electronic money (e-money) and cartal money (M0) on the velocity of money in Indonesia in 2010-2021. The type of data used in this study is quantitative and time series secondary data obtained from the publication of the bank Indonesia (BI) and Central Bureau Central (BPS). Data analysis techniques used multiple linear regression analysis with the program eviews 10. The hypothesis testing is carried out by statistical tests (t test, f test, coefficient of determination 2) and classical assumption test. The results of this study show that the electronic money transaction volume variable has a negative and insignificant effect on the velocity of money. The cartal money variable has a negative and significant effect on the velocity of money in Indonesia from 2010- 2021. Keywords : velocity of money, electronic money transaction volume, and cartal money (M0)